The Implementation of Restorative Justice in Minor Theft Cases Under Aceh Qanun Number 9 of 2008 on the Development of Customary Life and Traditions - Hartana , Hartana; T. Riza Zarzani; Fitri Rafianti (International Journal of Synergy in Law, Criminal, and Justice, 2025)
This study discusses the implementation of restorative justice in resolving petty theft cases in Aceh based on Aceh Qanun Number 9 of 2008 concerning the Development of Customary Life and Customs, with an emphasis on the role of village customary institutions and the support of regional regulations in strengthening the effectiveness of case resolution. The restorative justice paradigm is seen as an alternative to the retributive approach that has dominated the national criminal justice system, emphasizing the restoration of the original state, the responsibility of the perpetrator, and the involvement of victims and the community. In the context of Aceh, the position of customary institutions is legally recognized through Law Number 11 of 2006 concerning the Government of Aceh, Qanun Number 9 of 2008, and strengthened by the Joint Decree of the Governor of Aceh, the Chief of the Aceh Police, and the Aceh Customary Council in 2011–2012, and Aceh Governor Regulation Number 60 of 2013. These regulations provide a legal basis as well as technical guidelines for the implementation of village customary justice in handling petty theft cases through customary deliberations in the meunasah. The research method used is a socio-legal approach with literature review and observation, combining normative analysis of laws and regulations with empirical studies of social practices in the community. The results show that resolving petty theft cases through village customary courts is faster, cheaper, and more acceptable to the community, and is more effective in maintaining social harmony than formal justice. However, challenges remain, such as potential injustice in customary deliberations, limited documentation, and coordination with law enforcement officials. Therefore, guidance, supervision, and capacity building of customary institutions are needed to ensure the principles of restorative justice are truly realized. This study concludes that the Aceh model in integrating customary law with formal law can be a national reference in developing a more effective, humane, and local wisdom-based mechanism for resolving minor criminal cases.